The influence of perceived role ambiguity and school leadership prototypes on teachers’ anxiety about school leadership: The mediating role of leadership self-efficacy - Ayyıldız, Pınar; Fidan, Tuncer; Duyar, İbrahim; Arastaman, Gökhan; Kurt, Türker (Anales de Psicología / Annals of Psychology, 2025)
The purpose of the current study was to examine the influence of perceived role ambiguity and school leadership prototypes on teachers’ anxiety about pursuing school leadership positions. We also investigated the mediating role of teachers’ leadership self-efficacy beliefs. A random sample of 390 teachers participated in this cross-sectional correlational study. Multivariate statistics and structural equation modeling were employed to analyze the hypothesized direct and indirect relationship between the study variables. The findings demonstrated whilst the perceived role ambiguity significantly increased teachers’ anxiety about pursuing school leadership, school leadership prototypes decreased it. Leadership self-efficacy partially mediated the relationships between leadership prototypes and teachers’ anxiety about pursuing school leadership. The findings of the study would contribute to the development of policies that alleviate the adverse influence of the contributing factors to teachers’ reluctance to pursue leadership roles and promote their decisions to do so.